1063. Female sex and SARS-CoV-2 Serostatus Predict Nasopharyngeal RNA Clearance during Early COVID-19. (15th December 2022) - Moser, Carlee; Li, Jonathan Z; Eron, Joseph J; Aga, Evgenia; Daar, Eric S; Wohl, David A; Coombs, Robert; Javan, Arzhang Cyrus; Bender Ignacio, Rachel A; Jagannathan, Prasanna; Ritz, Justin; Sieg, Scott; et al.
Abstract: Background: Predictors of SARS-CoV-2 RNA levels and changes over time during early COVID-19 are not well characterized. Methods: ACTIV-2 is a phase II/III randomized, placebo-controlled, platform trial to evaluate investigational agents for treatment of COVID-19 in non-hospitalized adults. Participants enrolled within 10 days of symptom onset. Nasopharyngeal samples were collected for SARS-CoV-2 RNA testing on Days 0, 3, 7, 14 and 28; RNA was quantified with qPCR assay. SARS-CoV-2 seropositivity was defined as detectable IgG to any of nucleocapsid, receptor binding domain, S1 and S2 antigens by Bio-Plex multiplex assay. Censored linear regression and repeated measures Poisson models evaluated predictors of RNA including age, sex, race, ethnicity, risk of severe COVID-19, diabetes, BMI, obesity (BMI > 35 kg/m 2 ) and serostatus. Results: The study enrolled 537 participants from Aug 2020 to July 2021 at US sites. Median age was 48 years; 49% were female sex, >99% cis-gender, 83% white, 29% Hispanic/Latino, and 21% had BMI > 35 kg/m 2 . At Day 0, median symptom duration was 6 days, 50% were seropositive (2 were vaccinated) and 17% had RNA below the lower limit of quantification (LLoQ). Higher Day 0 RNA was associated with shorter symptom duration (Spearman correlation = -0.40, p< 0.001), as well as older age, white race, lower BMI and seronegativity, even when adjusting for symptom duration (all p< 0.03). Among the 203 on placebo with Day 0 RNA ≥ LLoQ, female sex had larger decreases in RNA at Day 3 vs male sex (difference in mean change: -0.8 log10 copies/mL (95% CI: -1.2, -0.4), p< 0.001) when adjusted for symptom duration and Day 0 RNA; this difference was also observed when evaluating the proportion with RNA < LLoQ at Day 3 (Risk Ratio (95% CI): 2.38 (1.11, 5.09)). Seropositivity at Day 0 was associated with higher probability of RNA < LLoQ at Days 3 and 7 (p< 0.001) in adjusted models. Seropositivity at Day 0 did not differ by sex. Conclusion: In this well characterized clinical trial cohort, shorter symptom duration, older age, white race, lower BMI and seronegativity were associated with higher RNA in early infection. Female sex and seropositivity were associated with earlier viral clearance. Further research is needed to determine if viral decay differences mediated by these host factors influence clinical outcomes. Disclosures: Joseph J. Eron, MD, Adagio Therapeutics: data safety monitoring committee|Gilead Sciences: Advisor/Consultant|Gilead Sciences: Grant/Research Support|Glaxo Smith Kline: Advisor/Consultant|Merck: Advisor/Consultant|ViiV Healthcare: Advisor/Consultant|ViiV Healthcare: Grant/Research Support Eric S. Daar, M.D., Gilead: Advisor/Consultant|Gilead: Grant/Research Support|GSK/ViiV: Advisor/Consultant|GSK/ViiV: Grant/Research Support|Merck: Advisor/Consultant|Merck: Grant/Research Support David A. Wohl, M.D., Gilead: Advisor/Consultant|Gilead: Grant/Research Support|Janssen: Advisor/Consultant|Lilly: Grant/Research Support|Merck: Grant/Research Support|ViiV: Advisor/Consultant|ViiV: Grant/Research Support Rachel A. Bender Ignacio, MD, MPH, Abbvie: Advisor/Consultant|SeaGen: Advisor/Consultant Justin Ritz, M.S., Alnylam Pharmaceuticals: Stocks/Bonds Urvi Parikh, PhD, Merck: Advisor/Consultant Judith S. Currier, M.D., MSc, Merck and Company: Advisor/Consultant Davey M. Smith, M.D., M.A.S., BAYER: Advisor/Consultant|Kiadis: Advisor/Consultant|Linear Therapies: Advisor/Consultant|Linear Therapies: Stocks/Bonds|MODEL MEDICINES: Advisor/Consultant|MODEL MEDICINES: Stocks/Bonds|Vx Biosciences: Advisor/Consultant|Vx Biosciences: Stocks/Bonds Kara W. Chew, M.D., M.S., Merck Sharp & Dohme: Grant/Research Support.